vault backup: 2025-02-16 19:02:21
This commit is contained in:
parent
763c9022ca
commit
c21c741225
27
.obsidian/plugins/obsidian-git/data.json
vendored
27
.obsidian/plugins/obsidian-git/data.json
vendored
@ -1,27 +0,0 @@
|
||||
{
|
||||
"commitMessage": "vault backup: {{date}}",
|
||||
"autoCommitMessage": "vault backup: {{date}}",
|
||||
"commitDateFormat": "YYYY-MM-DD HH:mm:ss",
|
||||
"autoSaveInterval": 5,
|
||||
"autoPushInterval": 0,
|
||||
"autoPullInterval": 5,
|
||||
"autoPullOnBoot": true,
|
||||
"disablePush": false,
|
||||
"pullBeforePush": true,
|
||||
"disablePopups": false,
|
||||
"listChangedFilesInMessageBody": false,
|
||||
"showStatusBar": true,
|
||||
"updateSubmodules": false,
|
||||
"syncMethod": "merge",
|
||||
"customMessageOnAutoBackup": false,
|
||||
"autoBackupAfterFileChange": false,
|
||||
"treeStructure": false,
|
||||
"refreshSourceControl": true,
|
||||
"basePath": "",
|
||||
"differentIntervalCommitAndPush": false,
|
||||
"changedFilesInStatusBar": false,
|
||||
"showedMobileNotice": true,
|
||||
"refreshSourceControlTimer": 7000,
|
||||
"showBranchStatusBar": true,
|
||||
"setLastSaveToLastCommit": false
|
||||
}
|
@ -15,6 +15,15 @@ If we have the coordinate pair $(a, f(a))$, and the value $h$ is the distance be
|
||||
$$\lim_{h \to 0}\dfrac{f(a + h) - f(a)}{h}$$
|
||||
The above formula can be used to find the *derivative*. This may also be referred to as the *instantaneous velocity*, or the *instantaneous rate of change*.
|
||||
|
||||
## Examples
|
||||
|
||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||
|
||||
1. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
||||
2. $= 4x^\frac{1}{3} - x^{-6}$
|
||||
3. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
||||
4. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
||||
5. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
||||
# Point Slope Formula (Review)
|
||||
$$ y - y_1 = m(x-x_1) $$
|
||||
Given that $m = f'(a)$ and that $(x_1, y_1) = (a, f(a))$, you get the equation:
|
||||
@ -114,9 +123,9 @@ $$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
||||
> Given the function $(x^2+3)^4$, find the derivative.
|
||||
|
||||
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
||||
1. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||
6. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
||||
2. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
||||
7. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
||||
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
||||
> Apply the chain rule to $x^4$
|
||||
|
||||
@ -152,18 +161,8 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
||||
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
||||
|
||||
Given these facts:
|
||||
1. Let $y$ be some function of $x$
|
||||
2. $\dfrac{d}{dx} x = 1$
|
||||
3. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
||||
What's the derivative of $y^2$?
|
||||
$\dfrac{d}{dx} y^2 = 2(y)^1 *\dfrac{dy}{dx}$
|
||||
8. Let $y$ be some function of $x$
|
||||
9. $\dfrac{d}{dx} x = 1$
|
||||
10. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
||||
|
||||
# Examples
|
||||
|
||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||
|
||||
4. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
||||
5. $= 4x^\frac{1}{3} - x^{-6}$
|
||||
6. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
||||
7. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
||||
8. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
||||
## Examples
|
||||
|
Loading…
x
Reference in New Issue
Block a user